Islamophobia: Radical Western Thoughts and it’s Encounter in the Light of Islam - Rafiq, Tehmina; Khan, Muhammad Kalim Ullah (Journal of Islamic and Religious Studies, 2021)
Islamophobia is an imposed term of the West broadly defined as a fear or hatred of Islam and its followers. Prejudice is considered an unjustifiable and harmful incident of discrimination that is related to the rise of Islamophobia. In western opinion, Muslims are warmongers who have extremist approaches towards life, and Islam is a backward religion. This radical mindset has relegated Muslims to an unimportant and powerless position within society and groups, which has triggered anti-Muslim sentiments among non-Muslims. Bullying, surveillance, fear, prejudgments against Muslims have been increased by schools, districts, landlords, and employees on the globe, especially in the western world. Mosque controversies in the United States, anti-veiling legislation in France, the 'minaret' row in Switzerland, the killing of Turkish immigrants in Germany, and hateful statements of Dutch politicians against Muslims are well-known examples of Islamophobia. The paper's primary purpose is to highlight the radical approach and anti-Muslim sentiments of the world in the name of Islamophobia. It will show Muslims are brutally targeted on every forum due to misperceptions regarding Islam and its teachings. Furthermore, the true spirit of Islam and its teachings are highlighted in this paper that Muslims are the ambassadors of peace, and Islam is the only religion of moderation that negates fanaticism and terrorist acts. In contrast, the rebellious acts of a few radical groups do not allow anyone to adopt hateful and intolerant attributes towards the whole nation.